Explaining individual changes in moral values and moral emotions among adolescent boys and girls - Sevensson, Robert (European journal of criminology, 2017)
In this study we examine to what extent within-individual changes in parental monitoring, bonds with parents and school, and rule-breaking peers can explain within-individual changes in morality. We distinguish between three key dimensions of morality: moral values, anticipated shame, and anticipated guilt. We use data from the SPAN project, a two-wave panel study among 616 adolescents (ages 12–19) from secondary schools in The Hague, The Netherlands. Employing a fixed-effects model, we found that within-individual changes in parental monitoring, bonds with parents and school, and rule-breaking peers are significantly related to within-individual changes in moral values, anticipated shame, and anticipated guilt. These findings emphasize the important role of family, school, and the peer group in the development of morality during adolescence. Implications of these findings are discussed.